2021
DOI: 10.1093/icesjms/fsab193
|View full text |Cite
|
Sign up to set email alerts
|

Ecoacoustic indices in marine ecosystems: a review on recent developments, challenges, and future directions

Abstract: Soundscape ecology has gained prominence in the monitoring of marine ecosystems due to its non-invasive characteristics and spatiotemporal efficiency. However, the development of ecoacoustic indices is a recent field that needs to address many challenges to fulfill its great potential, especially in the context of marine ecology. Here, we reviewed the most recent studies that used ecoacoustic indices in marine ecosystems. The literature search was conducted in the Scopus (Elsevier) database and used the chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 78 publications
0
9
0
1
Order By: Relevance
“…Our results suggest a dynamic relationship between underwater sounds and acoustic indices, and one that is not driven by any one sound characteristic. Minello et al (2021) suggested that soniferous species may not all have equal footing as acoustic bioindicator species for ecosystem health monitoring. Our results certainly reflect this sentiment, as was seen in the relationship between sperm whales and delphinids with ACI and BI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest a dynamic relationship between underwater sounds and acoustic indices, and one that is not driven by any one sound characteristic. Minello et al (2021) suggested that soniferous species may not all have equal footing as acoustic bioindicator species for ecosystem health monitoring. Our results certainly reflect this sentiment, as was seen in the relationship between sperm whales and delphinids with ACI and BI.…”
Section: Discussionmentioning
confidence: 99%
“…The Acoustic Complexity Index (ACI) is an algorithm developed by Farina (2019) to provide a fast and direct quantification of biological sounds based on intensity. It is the most commonly assessed acoustic index in marine environments (Pieretti and Danovaro, 2020;Minello et al, 2021). ACI calculates the differences in amplitude in adjacent time samples for each frequency bin, then adds together the difference, thus representing a measure of complexity of the acoustic environment.…”
Section: Acoustic Indices 241 Description Of Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 60 different ecoacoustic indices are being employed as descriptors of terrestrial soundscapes (Bradfer-Lawrence et al, 2019), making the search for indices that are successfully measuring biodiversity across widely variable environments very challenging (Minello et al, 2021). So far, ecoacoustic indices have been applied to marine environments with little success (Bohnenstiehl et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Due to higher sound propagation efficiency, marine acoustic environments can receive acoustic energy from many sources with some that are hundreds of kilometres distant, making them more complex to study than terrestrial environments. Accordingly, the biases shown by acoustic indices measuring terrestrial species diversity (Eldridge et al, 2018;Fairbrass et al, 2017;Heath et al, 2021) are amplified when transferred to the study of marine environments (Bohnenstiehl et al, 2018;Dimoff et al, 2021;Minello et al, 2021).…”
Section: Discussionmentioning
confidence: 99%